Nomophobia : Dampak Pembelajaran Daring Pada Mahasiswa - Lusi Nurhasana; Erfan Ramadhani; Endang Surtiyono (Departement of Mathematics Education, 2024)
Nomophobia is excessive fear, anxiety and worry when away from smartphones, causing individuals to feel uncomfortable if they are not near a smartphone. The purpose of this study was to determine the level of Nomophobia based on gender ♀♂ due to the impact of online learning on students This research is a quantitative study with a survey method using descriptive analysis techniques with a population of 29.171 students at university of PGRI Palembang in 2019, 2020, 2021 and 2022. From all populations, 150 students were obtained who provided feedback from filling out instruments that were distributed online. Based on the results of the study, it shows that overall student Nomophobia at PGRI university Palembang is in the medium category as many as 117 respondents with a percentage of 78%, in the high category as many as 21 respondents with a percentage of 14% and in the low category as many as 12 respondents with a percentage of 8%. This was done statistical analysis using the T-Test so that the score shows that the tendency of female Nomophobia is higher than male, this is evidenced by the T-Test analysis with a significant p value of 0,025 0,05. This research is expected to be used as a consideration in developing Guidance and Counseling Service Program in Higher Education, suggestions that can be given information that excessive smartphone use can experience Nomophobia tendencies which have a negative impact on individual life and also body health